Assessing the Optimality of a Three-Part Pricing Policy for an Asset-Sharing Platform in the Philippines - Mallari, Cristina Bianca (Archīum Ateneo, 2024)
One entry point to the circular economy is an asset-sharing platform that addresses issues on resource constraints and underutilized assets. In the platform, an implementing organization will provide easy access to underutilized assets such as cold storage and warehouse facilities to small-to-medium businesses. This paper assessed the optimality of a dynamic three-part pricing policy consisting of an activation fee, a subscription fee, and a cancellation fee, for Meron Exchange, an asset-sharing platform in the Philippines. It was determined that it is not optimal and not beneficial to charge an activation fee for the entire 20-year horizon. Meanwhile, charging a cancellation fee is not optimal at the start but later becomes beneficial but not yet optimal for the platform. Lastly, charging a subscription fee is beneficial for the platform for the entire horizon, but the exact optimal values are also yet to be determined.